Coronary endarterectomy: technique and results in a case-control study - Tyska,André Luiz (2003)
OBJECTIVE: Early reports showed a high incidence of postoperative morbidity and mortality after coronary endarterectomy, and its value is still controversial. With technical improvement the role of coronary endarterectomy has been reviewed. In this study we evaluate our results of coronary endarterectomy, and show our strategy for patients with diffuse coronary artery disease. METHOD: We retrospectively reviewed 278 patients who underwent coronary artery bypass grafting, between January 2000 and December 2001, separated in two groups. The endarterectomy group - 32 patients (11.5%) who underwent coronary endarterectomy and the control group of patients characteristics similar to the first group. RESULTS: The mean follow-up time was 9.9 months. Both groups only demonstrated a statistical difference in the number of previous myocardial infarctions. The coronary endarterectomy was performed on 38 vessels, 78.75% in the left coronary system, and 21.05% in the right system. In the postoperative follow-up no significant differences were detected, but in the coronary endarterectomy group the incidence of intra-aortic balloon pump insertion was higher. CONCLUSIONS: We demonstrated that coronary endarterectomy should be used to achieve complete revascularization in patients with diffuse coronary disease, and the results are similar to conventional surgical treatment. A long-term follow up is necessary to demonstrate the future performance of these vessels and grafts.